Virtual-Reality-Based Research in Hearing Science: A Platforming Approach - Pedersen,RL; Picinali,L; Kajs,N; Patou,F (AES Journal of the Audio Engineering Society, 2023)
The lack of ecological validity in clinical assessment, as well as the challenge of investigating multimodal sensory processing, remain key challenges in hearing science. Virtual Reality (VR) can support hearing research in these domains by combining experimental control with situational realism. However, the development of VR-based experiments is traditionally highly resource demanding, which places a significant entry barrier for basic and clinical researchers looking to embrace VR as the research tool of choice. The Oticon Medical Virtual Reality (OMVR) experiment platform fast-tracks the creation or adaptation of hearing research experiment templates to be used to explore areas such as binaural spatial hearing, multimodal sensory integration, cognitive hearing behavioral strategies, auditory-visual training, etc. In this paper, the OMVR’s functionalities, architecture, and key elements of implementation are presented, important performance indicators are characterized, and a use-case perceptual evaluation is presented.